Managing chemicals at the University of Limpopo : A safety perspective - Thivhafuni, Phumudzo Olga (University of Limpopo (Turfloop Campus), 2008)
Chemicals are found to be enormously dangerous on the health and safety criteria. In academic laboratories, chemical safety has always been a major concern. Safety risks are either not perceived at all, or perceived to be less dangerous than what they actually are. The climate of safety in any organization consists of employees’ attitudes towards, and perceptions of safety behaviour. In academic departments, safety is influenced by factors such as the organisational environment, management attitude and commitment, the nature of the job or task, and the personal attributes of the individual. This study is concerned with safety climate and chemical management practices in academic departments. More specifically, it investigates the safety perceptions, attitudes, and chemical management behaviours of university employees. It represents the empirical results of a questionnaire survey administered in a university department and direct observations of safe and unsafe chemical management behaviours, targeting employees who work with chemicals. Based upon the survey analysis results, this study demonstrates that employees in the academic departments under study have a good degree of risk awareness and a relatively high degree of safety consciousness. The results also reveal employees’ intentional unsafe chemical management behaviours. Further, it was found, empirically, that overall employees’ intentional unsafe behaviours seem to be best explained by employees’ perceptions of management attitude and commitment to safety, social and physical work environment, priority for safety, as well as their perception of the risk they are generally exposed to in their work environment. The study, thus, establishes that perceptions of management attitudes and actions have a direct effect on employees’ behaviour. There is a positive correlation between workers’ safety climate and chemical management safe behaviour in academic departments.
Thesis (MBA.) --University of Limpopo, 2008
Keywords: Chemicals management; Chemicals; Chemicals safety; 658.00711; Chemicals -- Safety measures